The Impact of Parasocial Relationships and Self-Congruity on Online Purchasing Decisions: The Mediating Role of Fear of Missing Out - Sijabat, Rosdiana (Journal of Ecohumanism, 2024)
The widespread adoption of digital technology has significantly altered consumer purchasing habits in the online arena. Online purchasing decisions have become critical to consumer behavior, involving various complex psychological, social, economic, and technological considerations. This study examines how three key factors, parasocial relationships (PR), self-congruity (SC), and fear of missing out (FoMO), influence online purchasing decisions (OPD). Structural equation modeling (SEM) was used to determine the influence of PR and SC on OPD and to discover any essential mediating factors in this association. Data was gathered empirically from 286 consumers who completed the entire online survey form. The results showed no statistically significant direct influence of PR or SC on OPD. However, this study found that FoMO is essential in mediating the interaction of PR, SC, and OPD. It implies that the association between PR and OPD is due to FoMO inclinations. As such, this work verifies FoMO's role as a mediator in the relationship between SC and OPD. The findings imply that a match between a person's self-congruity and a specific brand or product influences their online purchasing decisions through FoMO.